ULTRASOUND SHEAR WAVE ELASTOGRAPHY (SWE) FOR THYROID GLAND FOCAL LESION DIAGNOSIS - A. N. KATRICH; A. V. OKHOTINA; K. A. SHAMAKHYAN; N. S. RYABIN (Кубанский научный медицинский вестник, 2017)
We analyzed ultrasound examination results in 231 patients retrospectively. The first control group included 30 patients. The second group consisted of 201 patients with focal alterations in thyroid gland. According to elastography results we performed fine-needle aspiration and cytology examination. Analyzing morphological outcomes we defined following groups: colloid goiter – 92, cellular goiter – 54, Hashimoto disease – 44, thyroid cancer – 11 patients. Rigidity index (kPa) in the control group was: Ме – 13,75, LQ-UQ – (11,63–15,97), minimal – maximal data – 6,17–22,2; Rigidity indexes of tissue nodes were distributed as follows: colloid goiter Ме – 15,33, LQ-UQ – (12,97–19,17), minimal – maximal data – 3,57–42,67; cellular goiter – 16,40, (12,87 – 19,1), (5, 57-34, 6); autoimmune thyroiditis- 24,77, (17,13–29,57), (10,13– 68,0); thyroid cancer – 48,78 (21,63–57,67), (13,67–60,0). Threshold level for malignant mass was 44,2 kPA. Diagnostic accuracy for Еmean date in the groupd with thyroid cancer was 84,2 %.